Analisis Grammatical-Exegetical Wahyu 3:20 dan Implikasinya Terhadap Relevansi Penggunaan Wahyu 3:20 Dalam Model Penginjilan Kontemporer - Jhon Leonardo Presley Purba; Riang Hati Waruwu; Amran Manullang; Robinson Rimun (Jurnal Teologi Berita Hidup, 2022)
Revelation 3:20 is a popular verse that used in contemporary evangelism to encourage the unbelievers to believe in Jesus. Nevertheless, is such usage relevant to the text and context of Revelation 3:20? Using a descriptive qualitative research form with an interpretative model of Grammatical-Exegetical analysis, the aims of this study is to find the theological meaning of Revelation 3:20 and its implications for the relevance of the using of Revelation 3:20 in contemporary evangelistic models. The results of this study conclude that based on the text and context of Revelation 3:20, the usage of this verse in contemporary evangelism toward unbelievers is irrelevant to the text and its context, the meaning of "the door that knocks" by Jesus in this verse does not refer to the door of an individual's heart who do not know Christ but the "spiritual door" of the church or community of believers who have known Christ who are asked to repent from self-satisfied and lukewarmness because of physical wealth, this is also the true theological meaning of Revelation 3:20 which is very relevant with the moral and spiritual state of the church in the modern era which also tends to be self-satisfied and spiritually lukewarm so the implication for believers and the church today is the church need to repent from its self-satisfied, spiritual lukewarmness and "open its doors" for Christ so that Christ can come in to His church and live with His church.  Wahyu 3:20 merupakan ayat yang populer digunakan dalam penginjilan kontemporer untuk mendorong individu yang belum percaya menjadi percaya kepada Yesus. Namun, apakah penggunaan demikian relevan dengan teks dan konteks Wahyu 3:20? Menggunakan bentuk penelitian kualitatif deskriptif dengan model penafsiran analisa Grammatical-Eksegetical, penelitian ini bertujuan untuk menemukan makna teologis Wahyu 3:20 dan implikasinya terhadap relevansi penggunaan Wahyu 3:20 dalam model penginjilan kontemporer. Hasil penelitian ini menyimpulkan bahwa berdasarkan teks dan konteks Wahyu 3:20, penggunaan ayat ini dalam penginjilan kontemporer terhadap orang yang belum percaya tidak relevan dengan teks dan konteksnya, makna “pintu yang diketuk” oleh Yesus dalam ayat ini bukan merujuk pada pintu hati seorang individu yang belum mengenal Kristus melainkan “pintu rohani” gereja atau komunitas orang percaya yang telah mengenal Kristus yang diminta untuk bertobat dari berpuas diri dan suam-suam rohani karena kekayaan jasmani, inilah juga yang menjadi makna teologis yang sebenarnya dari Wahyu 3:20 yang sangat relevan dengan keadaan moral dan kerohanian gereja di era modern yang juga cenderung berpuas diri dan suam-suam secara rohani sehingga implikasinya bagi orang percaya dan gereja masa kini adalah agar gereja bertobat dari sifat berpuas diri, suam-suam rohani dan “membuka pintunya” bagi Kristus agar Kristus dapat datang kepada gereja-Nya dan tinggal bersama dengan gereja-Nya.